Fluorescence-Guided Sentinel Lymph Node Biopsy in Breast Cancer: Detection Rate and Diagnostic Accuracy - Vaz, Teresa (2018)
Introduction: Sentinel lymph node biopsy is currently the standard surgical procedure for lymph node staging in patients with early stage breast cancer. It is performed using different techniques, such as the injection of vital dyes and / or radioisotopes and, more recently, guided by fluorescence using Indocyanine green. The aim of this study is to assess the detection rate of sentinel lymph node using Indocyanine green in breast cancer patients according to factors related to the patient and the tumor.Material and Methods: Retrospective study of a random sample of patients with breast cancer, treated and followed at Centro Hospitalar São João, in Porto, between 2012 and 2016.Results: Indocyanine green detection rate was over 90% and its diagnostic accuracy was similar to other methods described in the presence of metastatic involvement of lymph nodes.Discussion: There was no statistically significant difference between the three methods in the detection rates in subgroups of older women, with normal weight and in those who underwent previous surgery in breast or axilla or neo-adjuvant chemotherapy.Conclusion: Indocyanine green is a potential alternative method to other sentinel lymph node screening techniques, appearing as a future option for breast cancer centers with no nuclear medicine department. However, it is essential to carry out further research in order to define the ideal patients’ profile that maximizes the method’s effectiveness.